AESTHETIC FEATURES OF EASTERN ROMANTICISM (Scientific journal of the Fergana State University, 2023)
In this article, the specific features of Eastern Romanticism aesthetics are expressed, and the essence of Eastern Romanticism is ideality, that is, a life in which Truth, Power and Peace prevail. In order to achieve Truth and Peace, the social foundations of Eastern romanticism appeared as an expression of this reality. In particular, it shows that Eastern romanticism is not only a specific historical event, but also a unique style and tradition in knowing the world.